Réponses

2013-01-03T00:04:27+01:00

C = A - B

= 9x² + 42x +49 - (25-20x+4x²)

= 9x² + 42x +49 - 25 +20x -4x²

C = 5x2+62x+24

 

C = A - B

= (3x+7)² -  (2x-5)²

= [(3x+7) + (2x-5)][(3x+7) - (2x-5)]

= (3x+7 + 2- 5) ( 3x+7 - 2x+5)

C = (5x + 2) (x + 12)

 

Pour x = 0

C = 5x2+62x+24

C = 24

 

Pour x = -1

C = (5x + 2) (x + 12)

= (5 × (-1) + 2) ((-1) + 12)

= (-5 + 2) × (11)

 = -3 × 11

C = -33

 

Pour x = -1/2

C = (5x + 2) (x + 12)

= (5 × (-1/2) + 2) ((-1/2) + 12)

= (-5/2 + 4/2) (-1/2 + 24/2)

= (-1/2) × 23/2

C = -23/4

 

C = (5x + 2) (x + 12)

= (5√3 + 2)(√3 + 12)

= 5√3 × √3 + 60√3 + 2√3 +24

= 5 × 3 + 60√3 +2√3 +24

= 15 + 24 + 60√3 +2√3

= 39 + 60√3 +2√3

C = 62√3 + 39

 

C =0

C = (5x + 2) (x + 12)

 

(5x + 2) (x + 12) = 0

 

⇔ (5x + 2) = 0         x +12 = 0

5x = -2                                x = -12

x = -2/5